Effects of Crude Shea Butters and Their Polar Extracts on Singlet Oxygen Quenching and Against Rose Bengal-Induced HaCaT Cell Phototoxicity - Bertrand W. F. Goumbri; Olivia Jansen; Roland Marini Djang’eing’a; Michel Frederich; Rasmané Semdé; Touridomon Issa Somé; Sabine Danthine; Ange Mouithys-Mickalad (Molecules)
Shea butter (SB) is a raw material fat obtained from Vitellaria paradoxa C.F. Gaertn kernels. We investigated the direct and indirect protective effects of 10 traditional and industrial SBs and their polar extracts on cell-free systems using ABTS and DPPH radical scavenging assays as well as on singlet oxygen (1O2) produced by Rose Bengal (RB) photosensitization. Their effects against RB-induced HaCaT cell phototoxicity were also explored. A spectrophotometric assay and HPLC were performed to quantify and identify phenolic content, which was between 14.16 and 82.99 ppm pyrogallol equivalent. These variations could be due to the SB origin and extraction process. These polar fractions exhibited moderate DPPH and strong ABTS radical-scavenging activity. By applying the UV–visible technique, we demonstrated that SBs and their phenolic compounds behave as 1O2 quenchers in a dose-dependent manner. Moreover, using a UVR-like model after the irradiation of RB, both polar extracts and crude SB exhibited photoprotective effects, highlighting the indirect protective action. In acellular and cellular models, SB and its polar extracts can act as a free radical scavenger against reactive oxygen species and 1O2 quenchers. Due to the maximum absorbance of SB at 280 nm and the antioxidant effect of 1O2 quenching, SB polar extracts exhibit photoprotective properties.